Systemic functional linguistics of eastern and western leaders' reaction towards trump's decision of recognizing Jerusalem as Israel Capital - Abdulameer, Ali Hussein (2021)
This study explored the journalistic stances of eastern and western social actors (leaders and representatives) towards the United States President Donald Trump's decision on Jerusalem as the capital of Israel in four online newspapers. The data were collected from four online newspapers, two newspapers from the east called Al Jazeera and The Star, while two from the west called New York Post and The Guardian. This study employed two theories from Systemic Functional Linguistics, the Transitivity system and the Appraisal system. This framework focused entirely on all the transitivity processes and attitude categories (Appreciation, Judgement, and Affect) to give the readers a new understanding of those political texts. This approach aimed to investigate the transitivity processes and evaluation in the stances of social actors (e.g., Presidents, Kings, Prime ministers, Ministers, and Ambassadors) among Trump's decisions on this issue. The current study selected eighty articles from four newspapers that were limited to one year from 6th December 2017 to 31st December 2018 after Trump's announcement regarding Jerusalem as the capital of Israel. The results showed that all eastern social actors were against Trump's decision, whereas some Western social actors supported the decision, such as Israel, Guatemala, Honduras, Marshall Islands, Micronesia, Nauru, Palau, and Togo. However, other western social actors were against the decision. The study also concluded that eastern and western social stances towards Trump's decision were represented more often in the Al Jazeera and The Star newspaper than in the New York Post and The Guardian. It concluded that eastern newspapers (Al Jazeera and The Star) are more concerned than western newspapers to show the stances of eastern and western social actors towards Trump's decision to the media and the whole world. Furthermore, the transitivity theory and the appraisal theory within SFL could play an essential role in analyzing the experiential meaning of social actors in political articles. It could also evaluate the political stance after the Trump declaration. These two theories have contributed to explore the experiential and interpersonal meaning in the discourse. Additionally, the methodology followed in the current study could be applied to different data sets in politics, such as presidential interviews, debates, and political conferences that could form rich data sets for testing the framework presented in this study. The present study, then, serves to help researchers concerned with political discourses in other texts and contexts. Finally, the study is an addition to literature, SFL in particular.